EFEKTIVITAS SENAM MATA TERHADAP COMPUTER VISION SYNDROME (CVS) - Intan Putri Arisandi; Gamya Tri Utami; Riri Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Computer vision syndrome (CVS) is one of the problems in the eye that causes serious eye disorders. This study aimed to identify the effect of eye exercise on CVS (Computer Vision Syndrome). This research is a quantitative research with quasy experiment research design. This research uses non equivalent control group design. The location of this research in Faculty of Nursing University of Riau. to student class A 2014. The study was conducted to students a 2014 with a Population of 120 respondents who are devided as 2 generation that is A 2014 1 and A 2014 2. The sample in this research is as many as 54 people who are divided into an experimental group and a control group who fit the inclusion criteria. the analysis was used independent sample t test and dependent sample t test. It can be concluded that effective eye exercises decrease CVS score (Computer Vision Syndrome). The results was showed a decrease to CVS in the experimental group after given eye exercise with p value (0,000) < α (0,05). This mean that eye exercise can reduce CVS symptoms. Eye exercise can was reduce CVS symptoms in non-pharmacological which can be independently, so was suggested to students who have other students can use complementary therapies to reduce CVS symptoms. Keywords: CVS (Computer Vision Syndrome), eye exercise, nursing students